2016
DOI: 10.1186/s40644-016-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTATATE and 18F-FDG PET/CT in Paraganglioma and Pheochromocytoma: utility, patterns and heterogeneity

Abstract: BackgroundPheochromocytomas (PCC) and paragangliomas (PGL) are neuroendocrine tumours arising from pluripotent neural crest stem cells and are associated with neurons of the autonomic nervous system. PCCs/PGLs are often hereditary and multifocal, and their biologic behaviour and metabolic activity vary making imaging of these tumours challenging. The imaging gold standard has been I-123 MIBG complemented by CT or MRI. PGLs being neuroendocrine tumours express somatostatin receptors enabling imaging with Ga-68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 43 publications
3
149
1
1
Order By: Relevance
“…Recent studies have reported high sensitivity using DOTATATE‐PET/CT for head and neck PGLs, especially tumours associated with SDHD mutations . This imaging modality is now recommended as the primary investigation for PGLs due to its high sensitivity and higher greater lesion to background contrast compared to FDG‐PET . However, as DOTATATE uptake is present in the normal adrenal glands, the sensitivity of Somatostatin receptor imaging (SRI) during primary assessment has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported high sensitivity using DOTATATE‐PET/CT for head and neck PGLs, especially tumours associated with SDHD mutations . This imaging modality is now recommended as the primary investigation for PGLs due to its high sensitivity and higher greater lesion to background contrast compared to FDG‐PET . However, as DOTATATE uptake is present in the normal adrenal glands, the sensitivity of Somatostatin receptor imaging (SRI) during primary assessment has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…12 This imaging modality is now recommended as the primary investigation for PGLs due to its high sensitivity and higher greater lesion to background contrast compared to FDG-PET. 13 However, as DOTATATE uptake is present in the normal adrenal glands, the sensitivity of Somatostatin receptor imaging (SRI) during primary assessment has not yet been established. With the expansion of theranostics and growing availability of Lutetium-177 (Lutate) peptide receptor radionuclide therapy (PRRT), a positive DOTATATE scan may provide guidance for treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Our experience also suggests utility for paragangliomas, 2 and it has been shown to be more sensitive than metaiodobenzylguanidine (MIBG) imaging, especially in patients with germline SDHB mutations. There is a greater reliance on imaging when clinical assessment is confounded by such factors, and our case illustrates the value of a multi-modality approach.…”
Section: Discussionmentioning
confidence: 85%
“…GaTate-PET/CT targets masses expressing somatostatin receptors and is widely used for evaluating neuroendocrine tumours. Our experience also suggests utility for paragangliomas, 2 and it has been shown to be more sensitive than metaiodobenzylguanidine (MIBG) imaging, especially in patients with germline SDHB mutations. 3 The lack of GaTate uptake in the intracranial mass made a paraganglioma metastasis unlikely given high uptake at other known sites of disease.…”
Section: Discussionmentioning
confidence: 85%
“…However, PRRT is highly recommended in patients with metastatic or inoperable NETs and positive expression of SSTR2 [11,22,23,24,25]. Although PRRT with radiolabeled somatostatin analogs is most commonly used for patients with WHO grade 1 and grade 2 gastrointestinal and bronchial NETs, patients with pheochromocytoma, paraganglioma, neuroblastoma, and medullary thyroid carcinoma may also benefit from the treatment [26,27,28,29]. …”
Section: Patient Selectionmentioning
confidence: 99%